The Role of Politics in Economic Development in Indonesia - Damay Rusli (Jurnal Restorasi : Hukum dan Politik, 2024)
The relationship between politics and economics is very close. Political democracy is also considered a condition for the functioning of economic democracy, where this process can be realized if there is parallelism between the political system and the economic system. The research method used by researchers includes descriptive analysis, based on a qualitative approach, so the results of this research explain that , the role of the political system becomes very important when development has a positive impact on economic welfare, where in this case economic growth becomes a barometer of the success of a country's economic development, but on the other hand, the success of economic development is seen from the success of achieving economic growth consciously or unconsciously. impact on the democratization side. The relationship between politics and economic development is very close, where both systems are studies that examine the relationship between political and economic phenomena, between the state and the market, between the domestic and international environment, and between government and society. Political democracy is also considered a condition for the functioning of economic democracy, and the implementation of economic democracy will be realized if there is alignment between the political system and the economic system.